Quick hits for new faculty : successful strategies by award winning teachers - Cordell, Rosanne M.; Lucal, Betsy; Morgan, Robin K., 1961-; Hamilton, Sharon J.; Orr, Robert H., 1942- (Quick hits, 2004)
Sound advice from award-winning college faculty.